MODEL GI-GI (GROUP INVESTIGATION-GUIDED INQUIRY) DALAM PEMBELAJARAN ELASTISITAS DI SMA (Studi pada Keterampilan Proses Sains dan Hasil Belajar Siswa) - Zulfi Nasirotul’Uma; Indrawati Indrawati; Yushardi Yushardi (FKIP Universitas Jember, 2017)
This research focuses on the implementation of GI-GI (Group Investigation-Guided Inquiry) model in elasticity learning at senior high school. This research aimed to describe student’s science process skills during using the model and to study affect the model on student’s physics learning achievement. This type of research is experiment research by post-test only control design. The population of this research is students of class XI IPA in SMAN Kalisat and the sample is two classes, XI IPA 3 as an experiment group and XI IPA 3 as a control group. Data collection techniques are observation, documentation, interview, and test. Data analysis techniques to describe student’s science process skills use descriptive analysis, to study affect the model on student’s physics learning achievement use independent sample t-test on SPSS 22. Finding this research are: (1) The average percentage of student’s basic science process skills is 69.14% included fairly good criteria, while the average percentage of student’s integrated science process skills is 81.96% included good criteria. (2) The significance value is 0,000 or <0.05 and it show that the model has a significant affect on student’s physics learning achievement. The research can be concluded that student’s basic and integrated science process skills during using GI-GI model are in fairly good criteria and good criteria. GI-GI model has a significant affect on student’s physics learning achievement. Key word: elasticity, GI-GI model, student’s learning achievement, student’s science process skills